Cognitive demands on geometrical tasks in Indonesian elementary school mathematics textbook - Yoppy Wahyu Purnomo; Masitah Shahrill; Olivia Pandansari; Rika Susanti; Winarni Winarni (Universitas Hamzanwadi, 2022)
Examples and exercises in mathematics textbooks have an essential role in directing teaching and learning to achieve the objectives of the mathematics curriculum. This study examines mathematical tasks, i.e., examples and exercises, for a grade 4 elementary school mathematics textbook published by the Indonesian Government in 2018. We focus on geometry tasks and categorize them based on the dimensions of cognitive processes and knowledge of the revised Bloom’s taxonomy. Textbook research is used to achieve the objectives of this study. The validity of the data was carried out by employing peer debriefing. The findings of this study indicate that only about 30% of the geometry tasks in this mathematics textbook require high-level mathematical thinking skills. This study also shows that procedural knowledge is more dominant and becomes an orientation in presenting geometry tasks. This finding becomes less relevant to the orientation of researchers and policymakers who want the direction of mathematics education to be forming students as problem solvers.